Intervensi Pekerja Sosial Dalam Menangani Kasus Anxiety Disorder Dengan Metode Cognitive Behavior Therapy - Umi Syalbiyah Natasya; Ati Kusmawati; Intan Putri; Cahyani Jinan Izdihar (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This journal discusses interventions carried out by social workers to treat someone who experiences anxiety disorders. Anxiety disorder is a type of mental health disorder such as feelings of fear, anxiety, restlessness and excessive worry that cannot be controlled and occur continuously so that they interfere with daily activities. There are many cases in Indonesia regarding people who have anxiety disorders. This must be treated and cannot be ignored, because if it is not treated, the sufferer will experience severe depression and even commit suicide. One of the professions responsible for this problem of social dysfunction is the social worker profession. Therefore, the aim of this journal is to explain the interventions carried out by social workers in treating someone who experiences anxiety disorders. This research method uses a qualitative approach with a literature study method. The social worker's intervention strategy uses the CBT (Cognitive Behavior Therapy) method which aims to eliminate the client's negative thoughts and be able to think rationally, apart from that, using behavior modification learning theory, namely systematic desensitization classical conditioning therapy by carrying out relaxation exercises so that the client is calmer when facing problems. conditions that make him anxious. The results of this research are interventions that social workers can carry out for people with anxiety disorders.